Age- and sex-specific impact on the progression of low-risk papillary thyroid carcinoma under active surveillance: a meta-analysis - Wang, Yang; Wang, Li (Frontiers in Oncology, 2025)
BackgroundThe global incidence of papillary thyroid carcinoma (PTC) is increasing significantly. In response, active surveillance (AS) has been promoted for Low-risk PTC owing to the absence of associated mortality. However, the association between age, sex, and risk of tumor progression remains unclear. This study aimed to assess the age- and sex-specific Impact on the progression of low-risk PTC.MethodsPubMed and Web of Science Core Collection were searched for articles published up to 1 January 2024. Articles reporting patients with PTC undergoing AS were included. Studies involving patients who underwent total or partial thyroidectomy or radiofrequency ablation were excluded. Random- and fixed-effect models were applied to obtain pooled proportions and 95% CIs.ResultsA total of 972 unique citations were screened and 39 full-text articles were reviewed, including eight cohorts. The mean or median age ranged from 41.5 to 53.1 years, with a predominant inclusion of female patients (76.39%–87.80%). The pooled risk ratio for tumor progression (a growth of 3 mm or more in maximal diameter or lymph node metastasis) in older adults (aged over 30–50 years) compared with younger individuals was 0.58 (95% CI, 0.47–0.71; 4,725 patients, six studies). However, for male patients, the pooled risk ratio for tumor progression compared with female individuals was 1.11 (95% CI, 0.64–1.93; 4,916 patients, six studies).ConclusionThis meta-analysis suggests that advanced age may be associated with a lower risk of progression of papillary thyroid microcarcinomas during active surveillance. No significant differences were observed between sexes.